Comment on "Pressure enhancement in carbon nanopores: a major confinement effect" by Y. Long, J. C. Palmer, B. Coasne, M. Śliwinska-Bartkowiak and K. E. Gubbins, Phys. Chem. Chem. Phys., 2011, 13, 17163. Issue 17 (27th April 2020) - van Dijk, David
Abstract : A standard thermodynamic interpretation unambiguously explains the observed properties of fluids confined in pores, while a "pressure enhancement" effect emerges only from calculations in which particular choices are selected from an arbitrary set. Abstract : In an article from Phys. Chem. Chem. Phys., 2011, 13, 17163, it is claimed that the microscopic local pressure is very high in a certain family of physical systems and that this phenomenon explains previously reported phase equilibrium and chemical reaction equilibrium data. The results provided in the article are based on two arbitrary choices. Thus, the results are arbitrary, and the conclusions appear to be unjustified.